2022
DOI: 10.1097/ta.0000000000003631
|View full text |Cite
|
Sign up to set email alerts
|

Data resources for evaluating the economic and financial consequences of surgical care in the United States

Abstract: Wanting to perform surgically-relevant health economics and health policy research, but not sure where to start? This review covers policy-relevant databases along with strengths, weaknesses, and examples of each. High-quality policy research has never been more important.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
14
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(15 citation statements)
references
References 88 publications
1
14
0
Order By: Relevance
“…It was able to identify four different financial trajectories after injury, including financially secure, financially frail, financially resilient, and financially devastated 23 . Noting the recovery and exacerbation patterns of FT and outcomes in these distinct trajectories, our findings on FT and health outcomes at a single time-point depict similar relationships and contribute further evidence supporting the bidirectional relationship of long-term health outcomes and FT for these patients 1,6 …”
Section: Discussionsupporting
confidence: 66%
See 4 more Smart Citations
“…It was able to identify four different financial trajectories after injury, including financially secure, financially frail, financially resilient, and financially devastated 23 . Noting the recovery and exacerbation patterns of FT and outcomes in these distinct trajectories, our findings on FT and health outcomes at a single time-point depict similar relationships and contribute further evidence supporting the bidirectional relationship of long-term health outcomes and FT for these patients 1,6 …”
Section: Discussionsupporting
confidence: 66%
“…This is compared with a similar study by Murphy et al 1 that sought to capture both objective and subjective components of FT; they found an FT prevalence of nearly 88% in their moderate to severely injured trauma patients in Memphis. Since people may experience financial hardship with only subjective measures, 6 our study may underestimate the prevalence of FT in our population.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations